(untitled) (Wageningen, 2019)
The aim of this research was to generate knowledge on how dietary macro-nutrients (with a focus on dietary carbohydrates) determine fish growth directly and indirectly (via natural food) in ponds.
Keywords: Cá,Fishes; Thức ăn và cho ăn,Feeding and feeds